Daur Ulang Plastik Menjadi Ekobrik Dalam Rangka Menunjang Program Green Campus UPI - Koosbandiah Surtikanti, Hertien; Hidayat, Topik; Surakusumah, Wahyu; Supriatno, Bambang; Marwati, Rini (Penerbit Goodwood, 2024)
Purpose: The aim of community service (PKM) is to empower and increase awareness of the entire academic community towards plastic waste. Research methodology: This PKM was carried out at Botanical Garden FPMIPA UPI. In order to maximize this activities, partners, namely the Himelnah Ciparay Community, Bandung Regency is invited. The method is followed by giving a lecture and workshop to 30 students These activities consists of (a) data survey on the use of tumblers in campus, (b) socialization and education about plastic waste and its risks, (c) collecting plastic bottles in the campus area, (d) recycling plastic bottles into ecobricks, (e) manufacture of products made from ecobricks and (f) feedback and responses from PKM activities. Results: After these activities, there were some changings such as improvement in students/people awareness level about plastic wastes; plastic bottles were collected in properly container (daily) at FPMIPA campus; water refill is facilitated at FPMIPA campus in order to minimize bottle plastics. Limitations: The limitation of this program is the number of volunteers who are not too many willing to be involved to take part in this event. Contribution: The contribution of this program includes instilling the habit of zero waste lifestyle to students to bring into their life, and also reducing the volume of plastic waste and preserving nature.